Gendered resilience in India’s seaweed farming: Highlighting policy lessons from the COVID-19 pandemic for inclusive Blue economy framework - Sundaram Swathi Lekshmi Perumal; Radhakrishnan Kalidoss; Gopal Nikita; D. Divu; Mojjada Suresh Kumar; V.P. Vipin Kumar; George Saju; S. Surya; R. Narayanakumar; Kingsly Jose; V.A. Leslie; S.S. Arabindoo; et al. (Marine Policy, 2026)

Metagenomic mining of microbial communication genes from Indian deep-sea sediments using a quorum sensing- and quenching-related protein database - D. Kesavan; Ramu Meenatchi; Raja Mohanakrishna; Anita Tripathi; Yashwanth B.S; Saravanane Narayanane; Saurav Gupta; Pushplata Yadav; Mukesh Pasupuleti; Greeshma Mani; Karpaga Raja Sundari Balachandran; Vijaya Raghavan Rangamaran; et al. (Marine Genomics, 2026)

Molecular insights into fibromyalgia: association of hub genes with pain targets, neuropathic pathways, and stress-related hormones - K. Gowri Gopal; Linda S Robi; D. R. Sherin (In Silico Pharmacology, 2026)

Application of a light detection and ranging digital elevation model for defining and mapping lakeshore riparian areas - T. Michalski; D. Sirk; L. Gopal (International Journal of Environmental Science and Technology, 2026)
In this study, a Light Detection and Ranging-based Digital Elevation Model was developed to delineate and assess the extent of lakeshore riparian environments across the Southwest regions of British Columbia, Canada. The analysis revealed substantial variability in riparian zone area and extent across diverse physiographic settings, with elevation emerging as the primary driver of riparian extent. Low-elevation lake basins were found to support substantially larger riparian areas, often with extensive wetlands. In contrast, high-elevation lake basins exhibited more confined riparian zones due to steeper topography. A legislated fixed-width riparian reserve did not capture the spatial extent of most modelled lakeshore riparian environments. The results of this study highlight the significant value of high-resolution terrain mapping and modelling data for defining the true extent of lakeshore riparian environments and inform conservation planning strategies for small lake ecosystems. The inclusion of a transferable framework for estimating riparian extent based on modeled median riparian width, elevation and physiographic criteria distinguishes this study from previous LiDAR‑based riparian mapping studies by offering an approach to estimating the extent of lakeshore riparian environments to land managers without access to LiDAR or other high-resolution spatial mapping techniques.

Perspectives on GUIDE (Guiding participation toward understanding, inclusion, diversity, and equity for cancer trials): a clinical trial access intervention - Kristine A. Karvonen; Jean A. McDougall; Sarah D. Hohl; Elizabeth A. Carosso; Tina Burrows; Solange H. Mecham; Elizabeth Stohr; Anne Devine; Hannah Linden; Ajay K. Gopal; Evan Y. Yu; Andrew J. Cowan; et al. (Cancer Causes & Control, 2026)

Pharmacogenomic, pharmacokinetic, and safety analysis of CYP3A4/CYP3A5 polymorphisms of midostaurin in patients with acute myeloid leukemia - Romain Sechaud; Thomas Peters; Helen Gu; Gholamreza Rahmanzadeh; Gopal Krishna Sharma; Nathalie Guichard; Hans D. Menssen (European Journal of Clinical Pharmacology, 2026)

Correlation between wastewater-based substance use prevalence and syringe distribution in a harm reduction program in the United States - Bikram Subedi; Houston D. Hampton; Joshua Revell; Kabita Kharel; Gopal Nath (Science of The Total Environment, 2025)

Potential and barriers of triterpenoid saponins as tomorrow´s plant based bio-pesticides - Søren Bak; Jan Günther; Pablo D. Cárdenas; Malboro Dervishi; Jincheng Shen; Rajeswari Gopal Geetha; Anja Fuglsang; Nina Cedergreen; Hans Chr. Bruun Hansen (Phytochemistry Letters, 2025)

Pseudomonas aeruginosa biofilm: treatment strategies to combat infection - Rashmi Ramesh; N. D. Rekha; Shubha Gopal (Archives of Microbiology, 2025)

Distribution and characterization of phytoplasmas infecting flower crops with diverse symptoms in Andhra Pradesh State, India - D. Meghanath; K. Arunodhayam; M. Gurivi Reddy; Ch. Ruth; M. Raja Naik; K. Gopal (Australasian Plant Pathology, 2025)

Predicting temperature variability in major Indian cities using Random Forest Regression (RFR) Model - Ashish Alone; Anoop Kumar Shukla; Gopal Nandan; D R Pattanaik (Journal of Earth System Science, 2025)

Estimating Soil Organic Carbon Using Sensors Mounted on Unmanned Aircraft System and Machine Learning Algorithms - Rahul Tripathi; Shiv Sundar Jena; Chinmaya Kumar Swain; Gopal Dutta; Bismay Ranjan Tripathy; Sangita Mohanty; P. C. Jena; Asit Pradhan; R. N. Sahoo; S. D. Mohapatra; A. K. Nayak (Journal of the Indian Society of Remote Sensing, 2024)

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Stalk rot species diversity and molecular phylogeny associated with diseased maize in India - J. Harish; Gopal Venkateshbabu; M. K. Prasannakumar; Pramesh Devanna; H. B. Mahesh; D. C. Balasundara; S. Dharanendra Swamy; Sridhara G. Kunjeti; C. Manjunatha; M. E. Puneeth; H. C. Lohithaswa; Prashant P. Jambhulkar (World Journal of Microbiology and Biotechnology, 2024)

Pre-Treated Crude Glycerol a Valuable Green Energy Source in the Era of Circular Bioeconomy—a Review - Gopal Bhukya; Sridhar Pilli; Sumanth Chinthala; R. D. Tyagi (Circular Economy and Sustainability, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

A green one-pot synthetic protocol of hexahydropyrimido[4,5-d]pyrimidin-4(1H)-one derivatives: molecular docking, ADMET, anticancer and antimicrobial studies - Harsh D. Trivedi; Bonny Y. Patel; Sanjay D. Hadiyal; Gopal Italiya; Prasanna Srinivasan Ramalingam (Molecular Diversity, 2024)

Environmental risk factors associated with the survival, persistence, and thermal tolerance of Cronobacter sakazakii during the manufacture of powdered infant formula - Rajni Chauhan; Ben D. Tall; Gopal Gopinath; Wamik Azmi; Gunjan Goel (Critical Reviews in Food Science and Nutrition, 2023)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Persistence and dissipation kinetics of novaluron 9.45% + lambda-cyhalothrin 1.9% ZC insecticides in tomato crop under semi-arid region - Abdul Rashid Khan Pathan; Bhanwar Lal Jakhar; Shish Ram Dhaka; Mukesh Nitharwal; Hanuman Singh Jatav; Ram Gopal Dudwal; Amit Kumar Yadav; Sandeep Kumar Choudhary; Vishnu Gauttam; Vishnu D. Rajput; Tatiana Minkina (Environmental Geochemistry and Health, 2023)

Wastewater-based surveillance can be used to model COVID-19-associated workforce absenteeism - Nicole Acosta; Xiaotian Dai; Maria A. Bautista; Barbara J. Waddell; Jangwoo Lee; Kristine Du; Janine McCalder; Puja Pradhan; Chloe Papparis; Xuewen Lu; Thierry Chekouo; Alexander Krusina; et al. (Science of The Total Environment, 2023)

A Web-Enabled Tool for Site Suitability Mapping for Managed Aquifer Recharge (MAR) Using Google Earth Engine (GEE) and Multi-Criteria Decision Analysis (MCDA) - Nitesh Patidar; Basant Yadav; Sumit Kumar; Abhay Raj; Gopal Krishan; Surjeet Singh; Bhaskar Jyoti Deka; Sanghyun Jeong; Ashish Pandey; Yutaka Matsuno; R. D. Singh (Water Resources Management, 2023)

Campus node-based wastewater surveillance enables COVID-19 case localization and confirms lower SARS-CoV-2 burden relative to the surrounding community - Jangwoo Lee; Nicole Acosta; Barbara J. Waddell; Kristine Du; Kevin Xiang; Jennifer Van Doorn; Kashtin Low; Maria A. Bautista; Janine McCalder; Xiaotian Dai; Xuewen Lu; Thierry Chekouo; et al. (Water Research, 2023)

Assessment of soil vulnerability to erosion in different land surface configurations and management practices under semi-arid monsoon climate - Gopal Kumar; R.S. Kurothe; A.K. Viswakarma; Debashis Mandal; Dipaka Ranjan Sena; Uday Mandal; V.C. Pande; D. Dinesh (Soil and Tillage Research, 2023)

Occurrences of UV filters, endocrine disruptive chemicals, alkyl phenolic compounds, fragrances, and hormones in the wastewater and coastal waters of the Antarctica - Keshava Balakrishna; Yerabham Praveenkumarreddy; D'Souza Nishitha; Chikmagalur Mallappa Gopal; Jayakrishna Kanhangad Shenoy; Krishnamurthy Bhat; Neloy Khare; Kiran Dhangar; Manish Kumar (Environmental Research, 2023)

Famished Frugivores or Choosy Consumers: A Generalist Frugivore (Wild Bornean Orangutans, Pongo pygmaeus wurmbii) Leaves Available Fruit for Nonfruit Foods - Andrea L. DiGiorgio; Yaxiong Ma; Elizabeth M. Upton; Sucharita Gopal; Natalie J. Robinson; TriWahyu Susanto; Cheryl D. Knott (International Journal of Primatology, 2023)

Unraveling the potential of bacteria isolated from the equatorial region of Indian Ocean in mercury detoxification - Gajendra Joshi; Pankaj Verma; Balakrishnan Meena; Prasun Goswami; D Magesh Peter; Dilip Kumar Jha; Nambali Valsalan Vinithkumar; Gopal Dharani (Frontiers in Marine Science, 2022)
The marine environment is most vital and flexible with continual variations in salinity, temperature, and pressure. As a result, bacteria living in such an environment maintain the adaption mechanisms that are inherent in unstable environmental conditions. The harboring of metal-resistant genes in marine bacteria contributes to their effectiveness in metal remediation relative to their terrestrial counterparts. A total of four mercury-resistant bacteria (MRB) i.e. NIOT-EQR_J7 ( Alcanivorax xenomutans ); NIOT-EQR_J248 and NIOT-EQR_J251 ( Halomonas sp.); and NIOT-EQR_J258 ( Marinobacter hydrocarbonoclasticus ) were isolated from the equatorial region of the Indian Ocean (ERIO) and identified by analyzing the 16S rDNA sequence. The MRBs can reduce up to 70% of Hg(II). The mercuric reductase (merA) gene was amplified and the mercury (Hg) volatilization was confirmed by the X-ray film method. The outcomes obtained from ICP-MS validated that the Halomonas sp. NIOT-EQR_J251 was more proficient in removing the Hg from culture media than other isolates. Fourier transform infrared (FT-IR) spectroscopy results revealed alteration in several functional groups attributing to the Hg tolerance and reduction. The Gas Chromatography-Mass Spectrometry (GC-MS) analysis confirmed that strain Halomonas sp. (NIOT-EQR_J248 and NIOT-EQR_J251) released Isooctyl thioglycolate (IOTG) compound under mercury stress. The molecular docking results suggested that IOTG can efficiently bind with the glutathione S-transferase (GST) enzyme. A pathway has been hypothesized based on the GC-MS metabolic profile and molecular docking results, suggesting that the compound IOTG may mediate mercuric reduction via merA-GST related detoxification pathway.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Variation of salinity in the Sundarbans Estuarine System during the Equinoctial Spring tidal phase of March 2011 - Meenakshi Chatterjee; D Shankar; V Vijith; G K Sen; D Sundar; G S Michael; P Amol; Abhisek Chatterjee; P Sanyal; Siddhartha Chatterjee; Anwesha Basu; Saranya Chakraborti; et al. (Journal of Earth System Science, 2021)

Diversity and biopotential of Bacillus velezensis strains A6 and P42 against rice blast and bacterial blight of pomegranate - Siddulakshmi Prasanna; M. K. Prasannakumar; H. B. Mahesh; Gopal Venkatesh Babu; P. Kirnaymayee; M. E. Puneeth; Karthik S. Narayan; D. Pramesh (Archives of Microbiology, 2021)

Comparative Evaluation of Patties Prepared from Pacific White Shrimps ( Litopenaeus vannamei ) Grown in Inland Saline Water and Brackish Water Regimes during Frozen Storage - D M Affarin Tinku; K.A. Martin Xavier; Binaya Bhushan Nayak; V. Hari Krishna; Gopal Krishna; Amjad Khansaheb Balange (Journal of Aquatic Food Product Technology, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Artificial night light alters ecosystem services provided by biotic components - Rajesh K. Singhal; Jyoti Chauhan; Hanuman S. Jatav; Vishnu D. Rajput; Gopal S. Singh; Bandana Bose (Biologia Futura, 2021)

Soil loss hinders the restoration potential of tree plantations on highly eroded ravine slopes - Raj Kumar; A. K. Bhardwaj; B. K. Rao; A. K. Vishwakarma; Vijaysinha Kakade; D. Dinesh; Gaurav Singh; Gopal Kumar; V. C. Pande; P. R. Bhatnagar; G. L. Bagdi (Journal of Soils and Sediments, 2021)

Tight sorption of arsenic, cadmium, mercury, and lead by edible activated carbon and acid-processed montmorillonite clay - Meichen Wang; Gopal Bera; Kusumica Mitra; Terry L. Wade; Anthony H. Knap; Timothy D. Phillips (Environmental Science and Pollution Research, 2021)

Measured and predicted acute toxicity of phenanthrene and MC252 crude oil to vertically migrating deep-sea crustaceans - Nicholas R. Turner; Gopal Bera; D. Abigail Renegar; Tamara M. Frank; Bernhard M. Riegl; José L Sericano; Stephen Sweet; Anthony H. Knap (Environmental Science and Pollution Research, 2020)

Marginalisation of off-grid energy sector in Sri Lanka: What lessons could be learnt? - Gopal K. Sarangi; D. Pugazenthi; Arabinda Mishra; Debajit Palit; Subhes C. Bhattacharyya (Environment, Development and Sustainability, 2020)

Correction to: Loop-mediated isothermal amplification assay for pre-symptomatic stage detection of Xanthomonas axonopodis pv. punicae infection in pomegranate - M. K. Prasannakumar; P. Buela Parivallal; C. Manjunatha; H. B. Mahesh; D. Pramesh; Karthik S. Narayan; Venkatesh Babu Gopal; K. Priyanka; M. E. Puneeth; K. T Rangaswamy (Australasian Plant Pathology, 2020)

Loop-mediated isothermal amplification assay for pre-symptomatic stage detection of Xanthomonas axonopodis pv. punicae infection in pomegranate - M. K. Prasannakumar; P. Buela Parivallal; C. Manjunatha; H. B. Mahesh; D. Pramesh; Karthik S. Narayan; Venkatesh Babu Gopal; K. Priyanka; M. E. Puneeth; K. T Rangaswamy (Australasian Plant Pathology, 2020)

Utilization of waste plastic oil in diesel engines: a review - D. Damodharan; B. Rajesh Kumar; K. Gopal; Melvin Victor De Poures; B. Sethuramasamyraja (Reviews in Environmental Science and Bio/Technology, 2019)

Transcriptome profiling of coriander: a dual purpose crop unravels stem gall resistance genes - Sharda Choudhary; Mahantesha B. N. Naika; Radheshyam Sharma; R. D. Meena; Ravindra Singh; Gopal Lal (Journal of Genetics, 2019)

High intraspecific genetic divergence in the versatile fairy shrimp Branchinecta lindahli with a comment on cryptic species in the genus Branchinecta (Crustacea: Anostraca) - Andres Aguilar; Alejandro M. Maeda-Martínez; Gopal Murugan; Hortencia Obregón-Barboza; D. Christopher Rogers; Kelly McClintock; Janice L. Krumm (Hydrobiologia, 2017)

Post heroin dose tissue distribution of 6-monoacetylmorphine (6-MAM) with MALDI imaging - Belin G. Teklezgi; Annapurna Pamreddy; Sooraj Baijnath; Nirmala D. Gopal; Tricia Naicker; Hendrik G. Kruger; Thavendran Govender (Journal of Molecular Histology, 2017)

Hydrogeological typologies of the Indo-Gangetic basin alluvial aquifer, South Asia - H. C. Bonsor; A. M. MacDonald; K. M. Ahmed; W. G. Burgess; M. Basharat; R. C. Calow; A. Dixit; S. S. D. Foster; K. Gopal; D. J. Lapworth; M. Moench; A. Mukherjee; et al. (Hydrogeology Journal, 2017)

Citrus yellow mosaic badnavirus infecting Citrus sp.: a threat to the citrus industry and a quarantine issue - A. M. Anthony Johnson; D. V. R. Sai Gopal; Chinta Sudhakar; Indranil Dasgupta (Journal of General Plant Pathology, 2017)

Adoption of Improved Rice Varieties in Nepal: Impact on Household Wellbeing - Nandakaji Budhathoki; Gopal D. Bhatta (Agricultural Research, 2016)

An efficient in vitro shoot regeneration from leaf petiolar explants and ex vitro rooting of Bixa orellana L.- A dye yielding plant - Arifullah Mohammed; Kishore K. Chiruvella; Nima D. Namsa; Rama Gopal Ghanta (Physiology and Molecular Biology of Plants, 2015)

Spontaneous Tumor Lysis Syndrome in an Infant: A Case Report - Mamatha T. Shenoy; Benedicta D’Souza; Lalesh Naik Akshatha; Vivian D’Souza; Madan Gopal Rajan (Indian Journal of Clinical Biochemistry, 2015)

Sequence analysis of Indian iris yellow spot virus ambisense genome segments: evidence of interspecies RNA recombination - S. J. Gawande; V. S. Gurav; A. A. Ingle; D. P. Martin; R. Asokan; J. Gopal (Archives of Virology, 2015)

Unusual and rare manifestations of dengue during a dengue outbreak in a tertiary care hospital in South India - M. Neeraja; V. lakshmi; V. D. Teja; Vanjari Lavanya; E. N. Priyanka; K. Subhada; M. M. Parida; P. K. Dash; Sashi Sharma; P. V. L. Rao; Gopal Reddy (Archives of Virology, 2014)

Effect of Actin Polymerization Inhibitor During Oocyte Maturation on Parthenogenetic Embryo Development and Ploidy in Capra hircus - R. Ranjan; R. K. Singh; T. Yasotha; Manish Kumar; Gopal Puri; Kuldeep Kumar; Renu Singh; Sanjeev Bhure; D. Malakar; S. K. Bhanja; M. Sarkar; B. C. Das; et al. (Biochemical Genetics, 2013)

Tidal variations in the Sundarbans Estuarine System, India - MEENAKSHI CHATTERJEE; D SHANKAR; G K SEN; P SANYAL; D SUNDAR; G S MICHAEL; ABHISEK CHATTERJEE; P AMOL; DEBABRATA MUKHERJEE; K SUPRIT; A MUKHERJEE; V VIJITH; et al. (Journal of Earth System Science, 2013)

The urban hydrology and hydraulic engineering at the classic maya site of Palenque - Kirk D. French; Christopher J. Duffy; Gopal Bhatt (Water History, 2013)

Current state of knowledge regarding the world’s wetlands and their future under global climate change: a synthesis - Wolfgang J. Junk; Shuqing An; C. M. Finlayson; Brij Gopal; Jan Květ; Stephen A. Mitchell; William J. Mitsch; Richard D. Robarts (Aquatic Sciences, 2013)

Analysis of full-length sequences of two Citrus yellow mosaic badnavirus isolates infecting Citrus jambhiri (Rough Lemon) and Citrus sinensis L. Osbeck (Sweet Orange) from a nursery in India - A. M. Anthony Johnson; B. K. Borah; D. V. R. Sai Gopal; I. Dasgupta (Virus Genes, 2012)

Hypoxia inhibition of camptothecin-induced apoptosis by Bax loss - Kyoungsook Park; Abdela Salah Woubit; Cesar D. Fermin; Gopal Reddy; Tsegaye Habtemariam; Jin Woong Chung; Minseo Park; Dai-Wu Seol; Moonil Kim (Biologia, 2012)

Production and characterization of somatic hybrids between Solanum tuberosum L. and S. pinnatisectum Dun. - D. Sarkar; Jagesh K. Tiwari; Sushruti Sharma; Poonam; Sanjeev Sharma; J. Gopal; B. P. Singh; S. K. Luthra; S. K. Pandey; D. Pattanayak (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Molecular and morphological characterization of somatic hybrids between Solanum tuberosum L. and S. etuberosum Lindl. - Jagesh K. Tiwari; Poonam; D. Sarkar; SK. Pandey; Jai Gopal; S. Raj Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Biological Control of Chickpea Collar Rot by Co-inoculation of Antagonistic Bacteria and Compatible Rhizobia - B. Hameeda; G. Harini; O. P. Rupela; J. V. D. K. Kumar Rao; Gopal Reddy (Indian Journal of Microbiology, 2010)

Association of a potyvirus with mosaic disease of gherkin (Cucumis anguria L.) in India - M. Srinivasulu; B. Sarovar; A. M. Anthony Johnson; D. V. R. Sai Gopal (Indian Journal of Microbiology, 2010)

Bioactive caffeic acid esters from Glycyrrhiza glabra - Surajit Dey; Mundkinajeddu Deepak; Manjunath Setty; Prashanth D’Souza; Amit Agarwal; Gopal Krishna Sangli (Natural Product Research, 2009)

Sequencing and computational analysis of complete genome sequences of Citrus yellow mosaic badna virus from acid lime and pummelo - Basanta K. Borah; A. M. Anthony Johnson; D. V. R. Sai Gopal; Indranil Dasgupta (Virus Genes, 2009)

Sodium-coupled Monocarboxylate Transporters in Normal Tissues and in Cancer - Vadivel Ganapathy; Muthusamy Thangaraju; Elangovan Gopal; Pamela M. Martin; Shiro Itagaki; Seiji Miyauchi; Puttur D. Prasad (The AAPS Journal, 2008)

Behavior of β-Cyfluthrin after Foliar Application on Chickpea (cicer aretinium L. ) and Pigeon Pea (cajanus cajan L.) - I. Mukherjee; M. Gopal; D. S. Mathur (Bulletin of Environmental Contamination and Toxicology, 2007)

Heavy Metal Uptake By Scirpus Littoralis Schrad. From Fly Ash Dosed and Metal Spiked Soils - Tanushree Bhattacharya; D. K. Banerjee; Brij Gopal (Environmental Monitoring and Assessment, 2006)

Interaction of Ibuprofen and Other Structurally Related NSAIDs with the Sodium-Coupled Monocarboxylate Transporter SMCT1 (SLC5A8) - Shirou Itagaki; Elangovan Gopal; Lina Zhuang; You-Jun Fei; Seiji Miyauchi; Puttur D. Prasad; Vadivel Ganapathy (Pharmaceutical Research, 2006)

Development of Core Subset of Finger Millet Germplasm Using Geographical Origin and Data on 14 Quantitative Traits - Hari D. Upadhyaya; C. L. L. Gowda; R. P. S. Pundir; V. Gopal Reddy; Sube Singh (Genetic Resources and Crop Evolution, 2006)

Effect of stereotactic ablation of the central nucleus of the amygdala on pain sensitivity among rats - Chandramouli Balasubramanian; Gopal Krushna Pal; D. B. Konar (Neurophysiology, 2006)

Conservation of unique patterns of body markings at ecdysis enables identification of individual spiny lobster, Jasus edwardsii - Alison B. MacDiarmid; Megan D. Oliver; Robert A. Stewart; Dharini Gopal (New Zealand Journal of Marine and Freshwater Research, 2005)
Southern temperate rock lobsters ( Jasus edwardsii ) develop complex body markings and spines that vary uniquely among individuals. These markings are retained after moulting allowing individuals to be recognised without capture or handling in the field. This enables the impact of capture, handling, and tagging procedures on subsequent movements to be more confidently evaluated. Recognition of individuals by natural markings allows post‐moult lobsters that were externally tagged and held in large communal tanks to be correctly retagged. Distinctive markings on the pedate processes and on the epistoma, as well as the number and placement of small spines on the antennular plate are particularly useful for recognising individuals. It is highly likely that the other Jasus species and the brightly patterned and coloured Panulirus species have similar body markings and spine patterns that would aid recognition of individuals.

Distribution of heavy metals in sediment and water of river Gomti - Vivek K. Gaur; Sanjay K. Gupta; S. D. Pandey; Krishna Gopal; Virendra Misra (Environmental Monitoring and Assessment, 2005)

Disappearance of Chlorpyrifos from Cultures of Chlorella vulgaris - I. Mukherjee; M. Gopal; D. W. Dhar (Bulletin of Environmental Contamination and Toxicology, 2004)

Recycling and Utilization of Metabolic Wastes for Energy Production is an Index of Biochemical Adaptation of Fish under Environmental Pollution Stress - K. Kamalaveni; V. Gopal; Ursula Sampson; D. Aruna (Environmental Monitoring and Assessment, 2003)

The Use of in Vitro Metabolic Stability for Rapid Selection of Compounds in Early Discovery Based on Their Expected Hepatic Extraction Ratios - Yau Yi Lau; Gopal Krishna; Nathan P. Yumibe; Diane E. Grotz; Elpida Sapidou; Laura Norton; Inhou Chu; Cliff Chen; A. D. Soares; Chin-Chung Lin (Pharmaceutical Research, 2002)

Role of the melanocortin-4 receptor in metabolic rate and food intake in mice - Airu S. Chen; Joseph M. Metzger; Myrna E. Trumbauer; Xiao-ming Guan; Hong Yu; Easter G. Frazier; Donald J. Marsh; Michael J. Forrest; Shobhna Gopal-Truter; Jill Fisher; Ramon E. Camacho; Alison M. Strack; et al. (Transgenic Research, 2000)

Soil Solarization: Technique for Decontamination of an Organophosphorus Pesticide from Soil and Nematode Control - M. Gopal; I. Mukherjee; D. Prasad; N. T. Yaduraju (Bulletin of Environmental Contamination and Toxicology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Fifty years of hydrobiological research in India - Brij Gopal; D. P. Zutshi (Hydrobiologia, 1998)

Electron microscopic evidence for the association of M 2 protein with the influenza virion - D. C. Jackson; Xi-Lin Tang; K. Gopal Murti; R. G. Webster; G. W. Tregear; W. J. Bean (Archives of Virology, 1991)

The effect of t-butylated hydroxytoluene on glutathione linked detoxification mechanisms in rat - Catherine A. Partridge; Dat D. Dao; Thomas D. Hong; Gopal Misra; Dean S. Folse; Yogesh C. Awasthi (Archives of Toxicology, 1983)